The Prospects of tumor necrosis factor α inhibitors use in patients with COVID-19 - E. S. Aronova; B. S. Belov (Современная ревматология)
The review highlights the problem of finding new effective treatment strategies for COVID-19. Tumor necrosis factor α (TNF-α) is considered as a therapeutic target. The theoretical basis for the successful use of TNF-α inhibitors (ITNFα) for the treatment of COVID-19 is presented, as well as data on existing practical developments, including ongoing clinical trials. Two drugs from the group of ITNFα – infliximab and adalimumab – are currently being considered as possible options. The safety issues of ITNFα treatment in patients with immunophaling rheumatic diseases and COVID-19 are discussed. The review also provides current data on vaccination against COVID-19, in particular on the vaccines currently available in Russia, which are at different stages of clinical trials. We conclude that randomized clinical trials of the effectiveness and safety of ITNF-α in patients with the new coronavirus infection are needed. Such trials will promote transition from theoretical speculations to real clinical practice.